IMPLEMENTATION OF A NON-CASH DISCLAIMER SYSTEM INSTUDY LOAN ADDITIONAL TRANSACTIONS AT UPC Pawnshop KALANGBRET (JANKA : Jurnal PengabdiAN Kepada MasyaraKAt, 2026)
This internship report discusses the implementation of a non-cash disbursement system for additional loan transactions at Pegadaian Kalangbret Service Unit (UPC). The transition from cash to non-cash disbursement is part of Pegadaian’s digital transformation to support the national cashless society program while improving service efficiency and financial transaction security. During the internship, direct observation was conducted on service procedures, customer requirements, disbursement stages, and both technical and non-technical challenges experienced in the field. The findings revealed that the system provides several advantages, including faster processing time, improved transaction security, and enhanced accuracy in financial records. However, challenges remain, such as customers’ lack of understanding of the new rules, limited bank ownership, additional fees for interbank transfers, and occasional system disruptions. Based on these observations, several recommendations are proposed, including continuous customer education, facilitation for opening partner bank accounts, strengthening digital infrastructure, and providing visual and written guidance. These measures are expected to optimize the system implementation and improve the overall quality of financial services in Pegadaian.Keywords: Pegadaian, Non-Cash System, Additional Loan, Digitalization, Financial Services.